Post‐Covid‐19‐vaccination adverse events and healthcare utilization among individuals with or without previous SARS‐CoV‐2 infection. (1st February 2022) - Lai, Francisco Tsz Tsun; Huang, Lei; Peng, Kuan; Li, Xue; Chui, Celine Sze Ling; Wan, Eric Yuk Fai; Wong, Carlos King Ho; Chan, Esther Wai Yin; Hung, Ivan Fan Ngai; Wong, Ian Chi Kei
Abstract: Background: Post‐marketing pharmacovigilance data are scant on the safety of Covid‐19 vaccines among people with previous SARS‐CoV‐2 infection compared with ordinary vaccine recipients. We compared the post‐vaccination adverse events of special interests (AESI), accident and emergency room (A&E) visit, and hospitalization between these two groups. Methods: We conducted a retrospective cohort study using a territory‐wide public healthcare database with population‐based vaccination records in Hong Kong. Results: In total, 3922 vaccine recipients with previous SARS‑CoV‑2 infection and 1, 137, 583 vaccine recipients without previous SARS‑CoV‑2 infection were included. No significant association was observed between previous SARS‑CoV‑2 infection and AESI or hospitalization. Previous SARS‑CoV‑2 infection was significantly associated with a lower risk of A&E visit (CoronaVac: hazard ratios [HR] = 0.56, 95% confidence intervals [CI]: 0.32–0.99; Comirnaty: HR = 0.62, 95% CI: 0.47–0.82). Conclusion: No safety signal of Covid‐19 vaccination was detected from the comparison between vaccine recipients with previous SARS‐CoV‐2 infection and those without infection.